Cleavage-Activation of Respiratory Viruses – Half a Century of History from Sendai Virus to SARS-CoV-2 - Takeda, Makoto (Japanese Journal of Infectious Diseases, 2024)
Many viruses require the cleavage-activation of membrane fusion proteins by host proteases in the course of infection. This knowledge is based on historical studies of Sendai virus in the 1970s. From the 1970s to the 1990s, avian influenza virus and Newcastle disease virus were studied, showing a clear link between virulence and the cleavage-activation of viral membrane fusion proteins (hemagglutinin and fusion proteins) by host proteases. In these viruses, cleavage of viral membrane fusion proteins by furin is the basis for their high virulence. Subsequently, from the 2000s to the 2010s, the importance of TMPRSS2 in activating the membrane fusion proteins of various respiratory viruses, including seasonal influenza viruses, was demonstrated. In late 2019, severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) emerged and caused a pandemic. The virus continues to mutate, producing variants that have caused global pandemics. The spike protein of SARS-CoV-2 is characterized by two cleavage sites, each of which is cleaved by furin and TMPRSS2 to achieve membrane fusion. SARS-CoV-2 variants exhibit altered sensitivity to these proteases. Thus, studying the cleavage-activation of membrane fusion proteins by host proteases is critical for understanding the ongoing pandemic and developing countermeasures against it.